2022
DOI: 10.1097/ju.0000000000002675
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Communication of Competing Risks of Mortality in Prostate Cancer Treatment Consultations

Abstract: Purpose:Men with prostate cancer prefer patient-specific, quantitative assessments of longevity in shared decision making. We sought to characterize how physicians communicate the 3 components of competing risks—life expectancy (LE), cancer prognosis and treatment-related survival benefit—in treatment consultations.Materials and Methods:Conversation related to LE, cancer prognosis and treatment-related survival benefit was identified in transcripts from treatment consultations of 42 men with low- and intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…20,21,33,34 Despite this strong preference for quantification of risk, we found that life expectancy, cancer prognosis, and side effects are often not quantified and are described using either generalizations (“high/low”) or omitted entirely 34%, 31%, and 62% to 93% of the time, respectively, on a per consultation level. 18,19 In the absence of risk quantification, the persuasive language used to describe these risks becomes the sole source of information for the patient to gauge whether the risks are acceptable or not. While the patient’s health numeracy and literacy are important in determining how risk information should be optimally communicated (e.g., with visual depictions such as icon arrays better than probabilistic descriptions in low numerate individuals), 35 in these patients, persuasive language alone should not be considered an acceptable substitute for communication of risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21,33,34 Despite this strong preference for quantification of risk, we found that life expectancy, cancer prognosis, and side effects are often not quantified and are described using either generalizations (“high/low”) or omitted entirely 34%, 31%, and 62% to 93% of the time, respectively, on a per consultation level. 18,19 In the absence of risk quantification, the persuasive language used to describe these risks becomes the sole source of information for the patient to gauge whether the risks are acceptable or not. While the patient’s health numeracy and literacy are important in determining how risk information should be optimally communicated (e.g., with visual depictions such as icon arrays better than probabilistic descriptions in low numerate individuals), 35 in these patients, persuasive language alone should not be considered an acceptable substitute for communication of risk.…”
Section: Discussionmentioning
confidence: 99%
“…10 We estimated that at least 20 patient consultations would allow for thematic saturation based on experience with our prior studies. 18,19 Patients were recruited until thematic saturation was reached, under which analysis of additional patients yielded no new codes (i.e., persuasive strategies). Of the total cumulative codes, 50%, 75%, and 90% of codes (persuasive strategies) were captured by subjects 3, 12, and 18, respectively (Supplementary Figure 1).…”
Section: Consultation Coding: Persuasive Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Four coders independently analyzed these quotes using an inductive coding approach to characterize SE type, mode of communication, and whether a timeline was mentioned. Our coding approach was informed by our expertise in prostate cancer treatment and our previous work, in which we characterized patient preferences [7] and physician variation in communication [6] of competing risks of mortality.…”
Section: Consultation Codingmentioning
confidence: 99%
“…We previously analyzed variation in communication of the survival benefit related to treatment-the "rewards" side of treatment tradeoffs-during treatment consultations and found substantial variation in the quality of risk communication [6]. In 40 consultations, physicians often failed to communicate the reduction in cancer mortality associated with treatment; cancer mortality was reported without treatment in 38%, with treatment in 10%, and in only 29% of consultations was cancer mortality reported both with and without treatment [6]. To our knowledge, there has been no similar analysis of how treatment-related SE are communicated by counseling physicians.…”
Section: Introductionmentioning
confidence: 99%